Stability of Uniformly Attracting Sets for Impulsive-Perturbed Multi-Valued Semiflows ⁎This work is partially supported by the German Research Foundation (DFG) and the State Fund for Fundamental Research of Ukraine (SFFRU) through the joint German-Ukrainian grant "Stability and robustness of attractors of nonlinear infinite-dimensional systems with respect to disturbances" (DA 767/12-1). Issue 2 (2020) - Dashkovskiy, Sergey; Kapustyan, Oleksiy; Perestyuk, Yuriy
Abstract: In this paper we investigate stability of uniformly attracting sets for semiflows generated by impulsive infinite-dimensional dynamical systems without uniqueness. Obtained abstract results are applied to weakly nonlinear parabolic system, whose trajectories have jumps at moments of intersection with certain surface in the phase space.